Post-COVID-19 tomographic abnormalities - Sawamura, M. V.Y.; Verrastro, C. G.Y.; Ferreira, E. V.M.; de Albuquerque, A. L.P. [UNESP]; Ribeiro, S. M. [UNESP]; Auad, R. V.; de Abreu Sperandio, P. C.; Souza, V. C.; Lima, M. L.; Prudente, R. A. [UNESP]; Franco, E. T. [UNESP]; Franco, A. C. [UNESP]; et al. (International Union Against Tuberculosis and Lung Disease, 2022)
BACKGROUND: The prevalence of persistent respiratory symptoms tends to be low in patients with a longer recovery time after COVID-19. However, some patients may present persistent pulmonary abnormalities.OBJECTIVE: To evaluate the prevalence of tomographic abnormalities 90 days after symptom onset in patients with COVID-19 and compare two chest high-resolution computed tomography (HRCT) analysis techniques.METHODS: A multicentre study of patients hospitalised with COVID-19 having oxygen saturation <93% on room air at hospital admission were evaluated using pulmonary function and HRCT scans 90 days after symptom onset. The images were evaluated by two thoracic radiologists, and were assessed using software that automatically quantified the extent of pulmonary abnormalities.RESULTS: Of the 91 patients included, 81% had at least one pulmonary lobe with abnormalities 90 days after discharge (84% were identified using the automated algorithm). Ground-glass opacities (76%) and parenchymal bands (65%) were the predominant abnormalities. Both chest HRCT technical assessments presented high sensitivity (95.9%) and positive predictive value (92%), with a statistically significant correlation at baseline (R = 0.80) and after 90 days (R = 0.36).CONCLUSION: The prevalence of pulmonary abnormalities on chest HRCT 90 days after symptom onset due to COVID-19 was high; both technical assessments can be used to analyse the images.